2017
DOI: 10.2147/ndt.s126100
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder in elementary school students in Shantou, China: prevalence, subtypes, and influencing factors

Abstract: Attention-deficit hyperactivity disorder (ADHD) is a frequent childhood-onset psychiatric condition and categorized into three subtypes of predominantly inattentive (ADHD-I), hyperactive impulsive (ADHD-H), and combined (ADHD-C). The prevalence and subtypes of ADHD vary considerably. The primary aim of this study was to provide a prevalence estimate of ADHD in elementary school students living in Shantou, a district of China, and in addition to examine the influence of informants, age, and gender on the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 42 publications
(51 reference statements)
8
24
3
Order By: Relevance
“…As controls, typically developing children from these same schools were randomly selected and matched according to gender and age to the cases. A two-stage screening procedure to diagnose children with ADHD was described in detail in our previous publication, 3 and shown in Figure S1 . Children with major physical diseases, bipolar disorder, psychotic disorder, and other severe psychiatric disorders were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As controls, typically developing children from these same schools were randomly selected and matched according to gender and age to the cases. A two-stage screening procedure to diagnose children with ADHD was described in detail in our previous publication, 3 and shown in Figure S1 . Children with major physical diseases, bipolar disorder, psychotic disorder, and other severe psychiatric disorders were excluded.…”
Section: Methodsmentioning
confidence: 99%
“… 2 The prevalence according to the criteria of DSM-5 is around 6% in China as well as in Shantou city. 3 …”
Section: Introductionmentioning
confidence: 99%
“…It assesses ADHD symptoms on a 4-point scale ranging from 0 to 3. It discriminates very well between children with and without ADHD and therefore has been used as a valid screening instrument for the identification and measurement of the behavioral problems of ADHD among children in China [ 19 ]. The total score is coded into a categorical variable, with a score ≥ 15 representing high levels of ADHD symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…This result further refines conclusions from previous voxel-based morphometry studies in which authors reported reduced gray matter in the motor and premotor cortices (38) There were several limitations of this study that need to be taken into account when interpreting the data. First, because of the low prevalence of the hyperactive impulsive subtype of ADHD in China (49) and our restrictive inclusion criteria, individuals with this subtype were not included in our study. Second, children of a fairly large age range who were at different stages of their developmental trajectories participated in our study.…”
Section: Figurementioning
confidence: 99%